2021
DOI: 10.1080/19476337.2021.1928757
|View full text |Cite
|
Sign up to set email alerts
|

Proximal analysis and profile of fatty acids on six varieties of white grain sorghum with potential use in human consumption

Abstract: In Mexico, corn is the most widely used cereal, however, in arid areas it is not possible to cultivate it, so white sorghum represents an alternative. However, it is important to know the varieties nutritional content. Therefore, this study the proximal profile and fatty acids of six white sorghum varieties grown in Mexico were evaluated. Proximate analysis was carried out based on AACC methods and gas chromatography had been used for fatty acid analysis. Mazatlan and Sureño varieties showed the highest conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…Los triacilgliceroles representan el 90%, siendo los ácidos linoleico, oleico y palmítico los más abundantes y en concentraciones más bajas están los ácidos mirístico y palmitoleico. El sorgo también presenta un alto contenido de ceras lipídicas (2.0 mg/g de grano), las cuales se componen de aldehídos grasos (44 a 55%), policosanoles (37 a 44%), ácidos grasos (4 a 8%), hidrocarburos (0.5 a 0.1%), ésteres de cera (1.4%) y triacilgliceroles (0.3 a0.4%) (Awika, 2017;Hums et al, 2018;Vanhercke et al, 2019;Treviño-Salinas et al, 2021).…”
Section: Lípidosunclassified
See 2 more Smart Citations
“…Los triacilgliceroles representan el 90%, siendo los ácidos linoleico, oleico y palmítico los más abundantes y en concentraciones más bajas están los ácidos mirístico y palmitoleico. El sorgo también presenta un alto contenido de ceras lipídicas (2.0 mg/g de grano), las cuales se componen de aldehídos grasos (44 a 55%), policosanoles (37 a 44%), ácidos grasos (4 a 8%), hidrocarburos (0.5 a 0.1%), ésteres de cera (1.4%) y triacilgliceroles (0.3 a0.4%) (Awika, 2017;Hums et al, 2018;Vanhercke et al, 2019;Treviño-Salinas et al, 2021).…”
Section: Lípidosunclassified
“…En la región de Asia, la producción de sorgo se centra en dos países, China (3.55 MT) e India (3.85 MT), los cuales producen el 94% del total en esta región. En América el principal país productor es Estados Unidos (9.474 MT), seguido de México (4.5 MT), Argentina (3.2 MT) y Brasil (2.1 MT) (Badigannavar et al, 2016;Teferra & Awika, 2019;Treviño-Salinas et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…This is associated with protective effects against several chronic-degenerative diseases (Wu et al, 2018;Slavin, 2004). It has also been shown that its consumption reduces cholesterol and triglyceride levels up to 50 % when this cereal is ingested by patients with hypercholesterolemia (Treviño-Salinas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%